Chronic alcohol intake upregulates hepatic expression of carotenoid cleavage enzymes and PPAR in rats - Luvizotto, Renata A. M.; Nascimento, André F.; Veeramachaneni, Sudipta; Liu, Chun; Wang, Xiang-Dong (Elsevier, 2010)
Excessive and chronic alcohol intake leads to a lower hepatic vitamin A status by interfering with vitamin A metabolism. Dietary provitamin A carotenoids can be converted into vitamin A mainly by carotenoid 15,15′-monooxygenase 1 (CMO1) and, to a lesser degree, carotenoid 9′10′-monooxygenase 2 (CMO2). CMO1 has been shown to be regulated by several transcription factors, such as the PPAR, retinoid X receptor, and thyroid receptor (TR). The regulation of CMO2 has yet to be identified. The impact of chronic alcohol intake on hepatic expressions of CMO1 and CMO2 and their related transcription factors are unknown. In this study, Fischer 344 rats were pair-fed either a liquid ethanol Lieber-DeCarli diet (n = 10) or a control diet (n = 10) for 11 wk. Hepatic retinoid concentration and expressions of CMO1, CMO2, PPARγ, PPARα, and TRβ as well as plasma thyroid hormones levels were analyzed. We observed that administering alcohol decreased hepatic retinoid levels but increased mRNA concentrations of CMO1, CMO2, PPARγ, PPARα, and TRβ and upregulated protein levels of CMO2, PPARγ, and PPARα. There was a positive correlation of PPARγ with CMO1(r = 0.89; P<0.0001) and both PPARγ and PPARα with CMO2 (r = 0.72, P< 0.001 and r = 0.62, P< 0.01, respectively). Plasma thyroid hormone concentrations did not differ between the control rats and alcohol-fed rats. This study suggests that chronic alcohol intake significantly upregulates hepatic expression of CMO1 and, to a much lesser extent, CMO2. This process may be due to alcohol-induced PPARγ expression and lower vitamin A status in the liver. © 2010 American Society for Nutrition.
Keywords: alcohol; carotenoid; carotenoid 15,15' monooxygenase 1; carotenoid 9'10' monooxygenase 2; peroxisome proliferator activated receptor; peroxisome proliferator activated receptor alpha; peroxisome proliferator activated receptor gamma; retinoid; retinoid X receptor; retinol; thyroid hormone; transcription factor; unclassified drug; acyl coenzyme A desaturase; beta carotene 15,15' monooxygenase; carotenoid 9',10' monooxygenase 2, rat; carotenoid 9',10'-monooxygenase 2, rat; messenger RNA; thyroid hormone receptor beta; alcohol consumption; alcoholism; animal experiment; animal tissue; concentration (parameters); controlled study; dietary intake; feeding; liquid; liver; male; nonhuman; nucleotide sequence; protein expression; rat; thyroid hormone blood level; upregulation; animal; blood; chemistry; drug effect; enzymology; Fischer 344 rat; genetics; Rattus; Animals; beta-Carotene 15,15'-Monooxygenase; Ethanol; Fatty Acid Desaturases; Liver; Male; Peroxisome Proliferator-Activated Receptors; PPAR alpha; PPAR gamma; Rats; Rats, Inbred F344; Retinoids; RNA, Messenger; Thyroid Hormone Receptors beta; Thyroid Hormones; Up-Regulation